3D Sapiotyping: A Three Dimensional Definition - Sanjay Kalra; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Precision medicine and personalized care have been at centre-stage in diabetology, and rightfully so. Various means of classification and clustering have been proposed to help identify clinical features, causative factors and ‘curative’ strategies for people living with diabetes. Sapiotype describes “the various attitudes that person with diabetes may have towards their disease, their doctor or health care providers, a specific diagnostic procedure, drug, delivery device, and the health care system at large”. The sapiotypic spectrum is a wide one, which encapsulates sapiotypic fluidity, or variability in attitudes, as well. In this communication, we further expand the sapiotypic spectrum by creating a 3- dimensional model.